Capital and ressentiment: The totalizing power of social fragmentation - Joseph Vogl (Finance and Society, 2021)
Joseph Vogl's new book, Capital and Ressentiment (2021/2022), traces an epistemic shift from knowledge to information driven by the convergence of financialization and the platform economy. As a variable that is determined less by semantic content than by difference to existing expectations, information invites indifference to other distinctions, such as those between fact and fiction, claim and proof. The circulation of information takes the form of opinion markets wherein the production of reality itself is at stake. In this extract, taken from the book's final chapter, "The cunning of ressentiment-driven reason", Vogl analyses populist ressentiment as both structural affect of and vital resource for information capitalism, laying out the resulting reconfiguration of the social.
Keywords: 300